2011
DOI: 10.1128/jvi.05859-11
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Neutralizing Cross-Reactive Antibodies against the Fusion Loop of West Nile Virus Envelope Protein ProtectIn Vivovia Fcγ Receptor and Complement-Dependent Effector Mechanisms

Abstract: The human antibody response to flavivirus infection is dominantly directed against a cross-reactive epitope on the fusion loop of domain II (DII-FL) of the envelope (E) protein. Although antibodies against this epitope fail to recognize fully mature West Nile virus (WNV) virions and accordingly neutralize infection poorly in vitro,their functional properties in vivo remain less well understood. Here, we show that while passive transfer of poorly neutralizing monoclonal antibodies (MAb) and polyclonal antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 87 publications
6
109
0
Order By: Relevance
“…1c) despite being incapable of neutralizing virus infectivity (Table 1). This result showed that WNV neutralizing activity of IVIG was not critical for protection from WNV encephalitis and that alternative mechanisms could mediate protection (Vogt et al, 2011), which we anticipated based on our demonstration that IVIG protection against HSV1 encephalitis was independent of neutralizing antibodies (Ramakrishna et al, 2011).…”
Section: A Single Dose Of Ivig Is Able To Protect From Lethal Wnv Infmentioning
confidence: 67%
See 1 more Smart Citation
“…1c) despite being incapable of neutralizing virus infectivity (Table 1). This result showed that WNV neutralizing activity of IVIG was not critical for protection from WNV encephalitis and that alternative mechanisms could mediate protection (Vogt et al, 2011), which we anticipated based on our demonstration that IVIG protection against HSV1 encephalitis was independent of neutralizing antibodies (Ramakrishna et al, 2011).…”
Section: A Single Dose Of Ivig Is Able To Protect From Lethal Wnv Infmentioning
confidence: 67%
“…IVIG has a broad repertoire of neutralizing antibodies for various pathogens and neutralization is commonly assumed to be the mechanism of protection against viral infection. However, we have shown in the HSV1 model that IVIG devoid of neutralizing antibodies is as effective as IVIG in protection against encephalitis (Ramakrishna et al, 2011) and the reports that non-neutralizing antibodies can protect against WNV infection are consistent with this (Chung et al, 2006;Mehlhop et al, 2005;Vogt et al, 2011). Studies investigating IVIG protection from WNV infection have based dosing on its neutralizing activity and have thus used IVIG at suboptimal doses (0.1-0.6 g kg 21 ) to elicit antiinflammatory responses.…”
Section: Introductionmentioning
confidence: 87%
“…One surface exposed by this 'breathing' is the fusionloop epitope (FLE), which is a dominant cross-reactive antigenic site 9 . Although antibodies to this site can protect by complement-mediated mechanisms, as shown in a mouse model for West Nile virus 10 , they are poorly neutralizing and lead to antibody-dependent enhancement [11][12][13][14][15] , thereby aggravating Flavivirus pathogenesis and complicating the development of safe and effective vaccines.…”
mentioning
confidence: 99%
“…S1B). The fusion loop has been described as a target for broadly cross-reactive antibodies against DENV (21,22) as well as other flaviviruses (23)(24)(25) and could be one of the epitopes targeted by the cross-reactive antibodies described in our study. In addition, despite the amino acid differences between the DENV2 and ZIKV E proteins compared, the two proteins share nearly identical structures (Fig.…”
Section: Denv-reactive Human Monoclonal Antibodiesmentioning
confidence: 99%